VARIABILITY IN THE NATURAL TERMITE RESISTANCE OF PLANTATION TEAK WOOD AND ITS RELATIONS WITH WOOD EXTRACTIVE CONTENT AND COLOR PROPERTIES - Lukmandaru, Ganis (Indonesian Journal of Forestry Research, 2011)
Property of natural termite resistance of teak (Tectona grandis)wood signifies one of its most important characteristics. With the purpose of understanding the variation in such resistance, four teak trees in the form of trunk (stem) from Randublatung , Central Java were randomly selected, and each wood portion sampled in radial and axial direction. Extractive content and color properties of the teak wood were also measured and correlated with properties of its natural termite resistance. Bioassay test was conducted by no-choice feeding method using Reticulitermes speratus Kolbe termites. The extractive contents were determined by successive extraction using n-hexane, ethyl acetate, and methanol, respectively. Color properties were measured with the CIELAB system. Results showed that antitermitic activity of the teak wood was affected by radial and axial position in the corresponding tree. The wood from middle part of the trees in axial direction exhibited the most resistant to termites (mean mass loss = 1- 4 mg ), while in radial direction the sapwood exhibited the least resistance ( greatest mass loss), and moving inward to the near-pith heartwood the resistance tended to decrease somewhat (slight increase of mass loss). Heartwood and sapwood part differed significantly in ethyl acetate and methanol- soluble extractive contents. Apparently, the greater the ethyl-acetate-soluble extractives (EEC) then the higher the termite resistant (lower mass loss), and conversely the greater the methanol- soluble extractive (MEC) then the lower the termite resistant ( greater mass loss). The brightness index (L*) and redness index (a*) varied significantly in radial direction, however, no significant variation was found in color properties within the heartwood. No strong degree correlation was measured between the mass loss due to termite activity and extractive content parameters. In both heartwood and sapwood, a significant negative correlation (r = -0.50) was found between the mass loss and redness (a*), while correspondingly a significant positive correlation (r = +0.54) occurred between brightness and mass loss. These occurring phenomena strongly suggested that the red colored teak wood was brought about by the moderately polar EEC (e.g. tannin, quinone, and other polyphenol) that inflicted teak-wood resistance against termite (lower mass loss), while the bright-colored teak wood was due to the highly polar MEC (e.g sugar and other soluble carbohydrate) which were conversely responsible for lowering termite resistance ( greater mass loss).